The Image of Sulṭān in Islamic Mirror of Princes - Fadi Zatari; Omar Fili (Darulfunun Ilahiyat)
This article seeks to explore the claims that al-Ādāb al-Sulṭānīyah literature legitimized tyranny, involving subverting religion to be a tool in the hands of political authorities and legitimizing the absolute authority of the ruler above the people, justifying his actions on a religious basis to establish an unquestioned and consequence-free rule. The article questions this approach for its anachronism and misunderstanding of al-Ādāb al-Sulṭānīyah literature’s nature and objectives regarding its views on political authority and tyranny. The work’s significant focus is the primary sources of al-Ādāb al-Sulṭānīyah authors to get a more comprehensive image in order to affirm whether there was a systematic effort to legitimize tyranny or whether it an affirmation of just rule. As a result of this study and a close reading of al-Ādāb al-Sulṭānīyah works, not only was it made clear that the al-Ādāb al-Sulṭānīyah genre and its authors did not intend to legitimize tyranny, but In fact, the genre and its authors vehemently opposed the transgressions of rulers.